ASSESSING ENGLISH TEACHERS’ ASSESSMENT LITERACY IN INDONESIA CONTEXT - Amalul Umam; Mutia Dara Malinda; Yani Awalia Indah; Movi Riana Rahmawanti (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2023)
Assessment literacy, the thorough understanding of assessment, is essential in education. However, the development of teacher assessment literacy in Indonesia has been alarmingly slow. This study investigated the development of teacher assessment literacy in English classes using a descriptive qualitative research design with 33 items related to basic assessment concepts. The results showed that there has been no significant change in the literacy level of English teachers in Indonesia. This low literacy level has not been seriously addressed by the government or education units, which has had various negative consequences for students and teachers alike